Optimal inter-stimulus interval for interpolated twitch technique when using double pulse stimulation - Karimpour, Rana (2013)
Interpolated twitch technique is a method frequently used to assess voluntary activa- tion. This method uses electrically evoked twitch superimposed on the voluntary activi- ty and its comparison with the twitch in rested muscle i.e. control twitch, to evaluate completeness of muscle activation. The purpose of this study was to investigate the ef- fect of interval in paired stimulation on control twitch in young and elderly individuals with bent and flexed knee positions. Supramaximal electrical stimulation consisted of one single stimulus and eight paired stimulation with intervals from 5 to 40ms, with increments of 5ms. In evoked twitches normalized peak torque amplitude (NPT), time to peak torque (TPT), half-relaxation time (HRT), maximal rate of torque development (RTD) were calculated. Although all parameters were slightly different in young adults compared to elder ones, the difference reached significance only in shorter TPT and HRT for the former, a phenomenon attributed to the slowing of muscle contractile me- chanics with ageing. In both groups the highest RTD and NPT were observed with shorter inter-stimulus intervals i.e. 5 and 10ms. This may be attributed to a summation effect and/or a less time available for the longer-latency reflex effects of electrical stim- ulation to affect the torque.